Autotaxin loss accelerates intestinal inflammation by suppressing TLR4‐mediated immune responses. (1st September 2020) - Kim, Su Jin; Howe, Cody; Mitchell, Jonathon; Choo, Jieun; Powers, Alexandra; Oikonomopoulos, Angelos; Pothoulakis, Charalabos; Hommes, Daniel W; Im, Eunok; Rhee, Sang Hoon
Abstract: Autotaxin (ATX) converts lysophosphatidylcholine and sphingosyl‐phosphorylcholine into lysophosphatidic acid and sphingosine 1‐phosphate, respectively. Despite the pivotal function of ATX in lipid metabolism, mechanisms by which ATX regulates immune and inflammatory disorders remain elusive. Here, using myeloid cell lineage‐restricted Atx knockout mice, we show that Atx deficiency disrupts membrane microdomains and lipid rafts, resulting in the inhibition of Toll‐like receptor 4 (TLR4) complex formation and the suppression of adaptor recruitment, thereby inhibiting TLR4‐mediated responses in macrophages. Accordingly, TLR4‐induced innate immune functions, including phagocytosis and iNOS expression, are attenuated in Atx‐deficient macrophages. Consequently, Atx −/− mice exhibit a higher bacterial prevalence in the intestinal mucosa compared to controls. When combined with global Il10 −/− mice, which show spontaneous colitis due to the translocation of luminal commensal microbes into the mucosa, myeloid cell lineage‐restricted Atx knockout accelerates colitis development compared to control littermates. Collectively, our data reveal that Atx deficiency compromises innate immune responses, thereby promoting microbe‐associated gut inflammation. Synopsis: Autotaxin is a secreted lysophospholipase that hydrolyzes lysophosphatidylcholine. Atx loss disrupts plasma membrane lipid rafts in macrophages, impairing TLR4‐induced innate immune responses, thereby accelerating gut inflammation. Atx loss disrupts membrane lipid rafts, thereby inhibiting TLR4‐mediated responses in macrophages. Atx deficiency suppresses the phagocytic activity of macrophages. Atx knockout mice have an elevated bacterial load in the intestinal mucosa and exhibit accelerated colitis. Abstract : Autotaxin is a secreted lysophospholipase that hydrolyzes lysophosphatidylcholine. Atx loss disrupts plasma membrane lipid rafts in macrophages, impairing TLR4‐induced innate immune responses, thereby accelerating gut inflammation.